Triticum durum Desf. is a valuable source for spring bread wheat genetic diversity enhancement - A. E. Druzhin; S. N. Sibikeev; E. I. Gultyaeva; L. B. Andreeva (Труды по прикладной ботанике, генетике и селекции)
Background. Enhancement of the Triticum aestivum L. genetic diversity by means of alien chromatin, including that from Triticum durum Desf., is an important element in the breeding of bread wheat cultivars that meet modern requirements.Materials and methods. The study included the L153, L154 and L155 introgressive spring bread wheat lines produced from crosses between the spring bread wheat cultivars ‘L503’ and ‘L505’ and spring durum wheat cultivars ‘Yazi10’ and ‘Tarro’ developed in Mexico. Evaluation of these introgressive lines included phytopathological, phenological, genetic, and breadmaking analyses carried out with conventional methods both under open-air and laboratory conditions. Seventeen DNA markers were used to identify genes for resistance to Puccinia triticina Erikss. f. sp. tritici in the lines. The obtained data were statistically analyzed using the Agros-2.10 package of breeding and genetic programs.Results. Studying introgressive spring bread wheat lines L153, L154 and L155, developed with the participation of durum wheat cvs. ‘Yazi10’ and ‘Tarro’, showed that leaf rust resistance of these lines was induced by the Lr genes from durum wheat cultivars. The effect of the gene donor and the recipient cultivars on a number of useful agronomic traits was identified. The recipient cv. ‘L505’ was noted for its good combining abilities.Conclusion. Introgression of chromatin from durum wheat cultivars into the spring bread wheat gene pool made it possible to produce lines resistant to the local P. triticina population, as well as to some test clones of this pathogen. Such lines can be used as donors of the Lr genes. In addition, the L154 introgressive line combined good grain productivity and baking quality.